Practical considerations for self-disclosure in applied sport psychology. Issue 1 (2nd January 2016) - Way, William; Vosloo, Justine
Abstract: Practitioner self-disclosure is a complex technique that can have tremendous influence—for better or worse—on an applied sport psychology consultation. Relative to the large body of literature in counseling and clinical psychology, few substantive resources are available to guide consultants' use of (or restraint from) self-disclosure in applied work with athletes. This article provides recommendations to begin filling that gap. Insights from existing literature are synthesized to provide practical guidelines and reflective considerations for the ethical and effective use of self-disclosure in applied sport psychology.